Gamifikasi Berbasis Audio untuk Pembelajaran Inklusif SDGs bagi Guru Tunanetra di Sekolah Negeri - Majidah Majidah; Alfian Akbar Gozali; Ranita Windriani (Universitas Muhammadiyah Palembang, 2025)
Education plays an essential role in producing quality graduates, and the right to quality education is guaranteed by law, including for people with disabilities. To realise quality education, teachers need to update their knowledge to equip students with the skills to understand environmental issues and, hopefully, obtain decent jobs, thereby contributing to sustainable, environmentally friendly economic growth. Therefore, it is necessary to conduct community service for visually impaired teachers on the Sustainable Development Goals for Visually Impaired Teachers using an audio-based gamification learning method, which is an innovative, inclusive learning method. Sixty special needs schoolteachers attended this community service activity, but only 65% participated in the assessment. The percentage of correct answers was relatively high, and the completion time was adequate. From each multiple-choice and true/false evaluation, five winners were selected based on the number of correct answers and the fastest completion time. The results of the audio-based assessment indicate that the learning materials and methods used were well absorbed.